Ritual objects and identity - Ventura i Oller, Monserrat (2000)
Shamanism, especially in the indigenous societies of South America, has been characterized by a complex system of material and symbolic inter-ethnic exchange. As part of this system, the objects used in shamanic rituals cannot be interpreted based on the meaning given by each particular culture from which they originate. Rather, they must be analyzed by the meaning that each receiving culture attributes to its supernatural world, which is usually represented by variable and diverse material forms. This theme will be illustrated with the ethnography of the Tsachila indigenous group from Ecuador, which deploys an extensive and complex network of shamanic exchanges.